The role of CT urogram and ultrasonogram in the evaluation of calculus obstructive uropathy - Hasmina, Kakoli; Mahtab, Masuma; Mondol, Sharmila; Afrin, Orin; Chaudhary, Mahesh (International Surgery Journal, 2025)
Background: Obstructive uropathy is a critical condition that requires prompt diagnosis, with imaging techniques like ultrasound and multidetector CT playing essential roles in evaluating urinary tract obstruction. The purpose of this study is to assess the effectiveness of CT urogram and ultrasonogram (USG) in diagnosing calculus obstructive uropathy. The aim of the study was to evaluate the effectiveness of CT USG in diagnosing calculus obstructive uropathy. Methods: This cross-sectional study was conducted at the Department of Radiology and Imaging, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from January to December 2018. It included 45 adult patients with clinically suspected calculus obstructive uropathy referred for USG and CT urogram. Imaging findings, including stone size, location, and hydronephrosis, were recorded, with CT urogram as the reference standard. Data were analyzed using SPSS to assess diagnostic accuracy, sensitivity, specificity, and predictive values. Results: The study of 45 patients, mostly male with a mean age of 35.8 years, found CT more effective than USG in diagnosing calculus obstructive uropathy. CT detected stones in 75% of patients with a sensitivity of 93.75% and specificity of 100%, whereas USG detected stones in 57.5% with a sensitivity of 61.29% and specificity of 88.88%. CT demonstrated superior diagnostic accuracy compared to USG. Conclusions: Unenhanced CT KUB shows higher diagnostic accuracy than USG in evaluating calculus obstructive uropathy, providing essential information for timely and accurate management.